O Serviço Social na efetivação dos direitos das pessoas com deficiência (PCD) no âmbito escolar - Silva, Ketyllene Santos (Brasil, 2023)
The research addresses Social Work in the realization of the rights of People with Disabilities (PCD) in the school environment. The objective of this work is to contribute to the discussion about the role of the social worker in educational inclusion and how this professional's performance will be important for the attempt to enforce the rights of students with disabilities, which was carried out through an exploratory bibliographical research. in books, articles, scientific journals and legislation that supported the proposed theme. The specific objectives are: To highlight inclusion policies and their applicability to students with special educational needs, ranging from the history of inclusive education in Brazil as well as specific legislation; Evidence of Social Work and education, presenting brief considerations about the profession, anti-disability and highlighting important points of Social Work in education; Follow up on questions about professional social workers in education and, based on Law 13,935/2019, their performance; Reveal the challenges and possibilities of the social worker's role in the education of people with disabilities. The study shows that social workers have a real challenge when developing their intervention in terms of inclusion in the educational area. Guidance on the attributions of social workers is very important for the proper development of actions at school and in the community and serves as a parameter for the professional's activities. Therefore, to see inclusion reflected within an educational institution, the social worker must encourage a participatory environment, without discrimination, for the uncompromising defense of human rights, where students, families and competent professionals are involved, in the perspective of a society free of prejudices, anti-capacitist and inclusive.